IMPLEMENTASI ALGORITMA MULTIPLICATIVE CRNG (CONGRUENTIAL RANDOM NUMBER GENERATOR) PADA APLIKASI TES KEMAMPUAN DASAR KOMPUTER MENGGUNAKAN PHP - wahyu illahi illahi (NUANSA INFORMATIKA, 2016)
TKD is a test derived from the State Personnel Board (BKN). This test consists of three parts namely General Intelligence Test (TIU), National Insight Test (TWK), and Personal Characteristic Test (TKP). TKD is intended to explore the knowledge, skills, and attitude / behavior of Civil State Apparatus candidate (ASN) to get civil servants who have good skills so that they can work professionally later. The implementation of TKD uses computer-based system using CRNG Multiplicative Algorithm (Congruential Random Number Generator). Where the algorithm is used to randomize the numbers that can not be predicted emergence. The programming used for this TKD application uses PHP programming which explains that PHP scripts can be embedded script that puts the PHP tag between HTML tags while non embedded script that is all HTML tags are placed in PHP tags. So the application of algorithms in PHP-based TKD application will allow random or random questions raised, which later about TKD on one computer with another computer will produce different problem numbers